2015
DOI: 10.4238/2015.december.11.6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of CYP2B6 polymorphisms in Argentinians: the role of genetic testing

Abstract: ABSTRACT. CYP2B6 is a highly polymorphic isoenzyme involved in the metabolism of many drugs including cyclophosphamide, bupropion, and efavirenz. A single nucleotide polymorphism (SNP) in CYP2B6 (516G>T) resulted in decreased expression and function associated with the CYP2B6*6 haplotype. Among the clinical implications of this phenotype, decreased activation of cyclophosphamide and increased plasma levels of efavirenz associated with increased central nervous system toxicity have been reported. The frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 11 publications
(9 reference statements)
1
8
0
Order By: Relevance
“…Sexual differences in the distribution of genotypes were not observed. Genotyping should be used as an additional tool for personalized medicine in connection with the high prevalence of the TT genotype in the studied population (Scibona et al, 2015). The study conducted in China determined the frequency of CYP2B6 516G/T mutation in 79 HIV infected patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sexual differences in the distribution of genotypes were not observed. Genotyping should be used as an additional tool for personalized medicine in connection with the high prevalence of the TT genotype in the studied population (Scibona et al, 2015). The study conducted in China determined the frequency of CYP2B6 516G/T mutation in 79 HIV infected patients.…”
Section: Resultsmentioning
confidence: 99%
“…The CYP2B6 is one of the members of the cytochrome P450 superfamily. This enzyme metabolizes a number of currently prescribed drugs and different compounds, such as nicotine (Yamazaki et al, 1999), cyclophosphamide, bupropion, efavirenz (Scibona et al, 2015) and ketamine (Li et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Africa, the overall frequency of the G and T alleles is 65% and 35%, respectively, and that of genotypes GG is 42%, GT is 45%, and TT is 13% (Scibona et al, 2015). Arnaldo et al demonstrated a large variation in the distribution of different CYP2B6 variants in Mozambique including the G516T substitution (Arnaldo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%